Characterizing Habitat Suitability of Long‐Finned Pilot Whales in a Key Conservation Region of the Southern Iberian Peninsula Using Satellite Tracking Data - Jazel Ouled‐Cheikh; Edgard Ballesta; David March; Pedro García; Philippe Verborgh; Renaud de Stephanis; Joan Giménez (Marine Mammal Science, 2026)
The waters surrounding the southern Iberian Peninsula are a key conservation area for the long‐finned pilot whale ( Globicephala melas melas ), particularly in the pelagic regions of the Strait of Gibraltar, the Alboran Sea, and the Gulf of Vera, where upwelling, complex bathymetry and frontal dynamics enhance productivity and prey availability, attracting cetaceans year‐round. This study presents the first published satellite tracking data for this species in the Mediterranean Sea, with six individuals tracked between March and November 2011 (21–93 days; 235–410 filtered locations per individual). We used boosted regression trees to model habitat suitability and identify the environmental factors associated with the distribution of long‐finned pilot whales. To evaluate the relative importance of physiographic features and oceanographic conditions, we fitted three models using static predictors, dynamic predictors, and both combined. The combined model showed the highest predictive accuracy (AUC = 0.87), followed by the static‐only (0.86) and dynamic‐only models (0.73). Habitat suitability was primarily driven by bathymetry and distance to shore, with whales preferentially using the continental slope (500–1500 m depth) near the shelf break. Among oceanographic variables, eastward surface currents were positively associated with habitat suitability, likely reflecting Atlantic inflow sustaining frontal systems and prey aggregation in the Alboran Sea. These findings can inform conservation planning and prioritization within existing protected areas.

Abundance trends of French tropical tuna purse seine fisheries bycatch species in the Eastern Atlantic Ocean - Clara Lerebourg; David March; Philippe S. Sabarros; David M. Kaplan (Fisheries Research, 2026)

Testing Mesoproterozoic continental suture models for central Australia using Lu–Hf garnet geochronology and mineral equilibria modelling - Samantha March; Martin Hand; Laura Morrissey; David Kelsey (Gondwana Research, 2026)

Artificial intelligence enhanced litter pollution mapping: Integrating citizen science with geospatial and social data - Hadiseh Rezaei; Keiron. P. Roberts; Farzad Arabikhan; Steve Fletcher; Antaya March; Fay Couceiro; David Bacon; David. J. Hutchinson; John. B. Williams (Environmental Modelling & Software, 2026)

Key drivers of at‐vessel mortality in demersal sharks - David Ruiz‐García; Claudio Barría; Juan A. Raga; David March (Conservation Biology, 2026)
Chondrichthyans are highly vulnerable to fisheries overexploitation, and postcapture mortality poses a significant threat to most species. Global bycatch mitigation guidelines recommend adopting hierarchical decision‐making approaches tailored to species‐specific vulnerabilities and socioeconomic and regulatory contexts. Effective implementation of such strategies requires robust understanding of the factors driving vulnerability to postcapture mortality. To address this need, we developed a machine learning method to identify key drivers of at‐vessel mortality (AVM) based on a broad set of biological, environmental, and fishing‐related parameters. We sought to reveal interactions among predictors, nonlinear responses between these variables and mortality risk, and threshold values beyond which the likelihood of mortality increased markedly. We applied this approach to trawl bycatch data on small‐spotted catshark ( Scyliorhinus canicula ) and blackmouth catshark ( Galeus melastomus ) in the western Mediterranean. Body size, air temperature, and on‐deck time emerged as the primary AVM drivers. Mortality risk increased substantially at temperatures above 20°C for S. canicula and 16°C for G. melastomus , with on‐deck exposure exceeding 15 min, and when body size was below 40 and 55 cm, respectively. Identification of these drivers and thresholds provides valuable insights for bycatch mitigation; can inform strategies for more threatened, closely related, or physiologically and ecologically similar species; and may support management authorities in adopting targeted bycatch avoidance strategies, gear selectivity, and mortality reduction measures. Such measures can be tailored to specimens, areas, and periods of heightened mortality risk to maximize effectiveness. Furthermore, our scalable modeling approach offers a robust tool for identifying critical AVM drivers across regions and species, and its applicability can be extended to broader fisheries management and global conservation efforts.

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Seamounts of Cabo Verde: A review of their ecological and economic significance, anthropogenic impacts, and conservation needs - Covadonga Orejas; Beatriz Vinha; Gillian B. Ainsworth; Sarah Saldanha; Teresa Militão; Christian Mohn; Thor H. Hansteen; Sara S. Ratão; Henk-Jan Hoving; Teresa Amaro; Dominique M.J. Anderson; Deusa Araújo; et al. (Progress in Oceanography, 2026)

Leveraging Earth Observation Data to Monitor Boat‐Based Recreational Fishing - Javier Menéndez‐Blázquez; Mara Segovia; David March (Fish and Fisheries, 2025)
Recreational fishing is widespread in coastal zones and exerts significant ecological, fisheries‐related and socio‐economic pressures. Unlike commercial fishing, small‐scale recreational fleets are challenging to monitor because they lack enforced use of vessel tracking systems such as the Automatic Identification System (AIS). Recently, remote sensing technologies have emerged as promising alternatives for monitoring marine activities. Here, we assess the potential of high spatio‐temporal resolution satellite imagery to monitor daily changes in recreational fishing boats during a temporal fishing ban within a marine protected area. By comparing satellite‐derived boat detections with AIS records, we demonstrate that satellite data can reliably capture daily changes in recreational fishing activity missed by AIS, including a marked increase immediately following the end of the ban. These findings confirm that satellite observations can consistently detect small fishing boats and reveal their fine‐scale spatio‐temporal patterns. When complemented with local knowledge, this approach enhances our capacity to contribute to the spatial planning and ecosystem‐based management of recreational fisheries.

Neighbour perspectives on cultural ecosystem services of blue-green infrastructures: The ecovillage Hannover, Germany - Andrea Nóblega-Carriquiry; Hug March; David Sauri; Jochen Hack (Ecosystem Services, 2025)

Potential Spatial Mismatches Between Marine Predators and Their Prey in the Southern Hemisphere in Response to Climate Change - Maria Bas; Jazel Ouled‐Cheikh; Alba Fuster‐Alonso; Laura Julià; David March; Francisco Ramírez; Luis Cardona; Marta Coll (Global Change Biology, 2025)
Global change is rapidly reshaping species' habitat suitability ranges, hence leading to significant shifts in the distribution of marine life. Contrasting distributional responses among species can alter the spatial overlap between predators and prey, potentially disrupting trophic interactions and affecting food web dynamics. Here, we evaluate long‐term changes in the spatial overlap of habitat suitability ranges for trophically related species, including crustaceans, fish, penguins, and pinnipeds across 12 Large Marine Ecosystems from the Southern Hemisphere, merged into three primary regions: South America, Southern Africa, Australia and New Zealand. To this aim, we first use Boosted Regression Trees (BRTs) to hindcast and project species‐specific changes in suitable habitat from 1850 to 2100 under two future climate scenarios: SSP1‐2.6 (low climate forcing) and SSP5‐8.5 (high climate forcing). We then analyze changes in species habitat suitability and potential predator–prey spatial overlaps. Findings reveal that marine species generally exhibit changes in their suitable habitats, with pronounced shifts towards higher latitudes under the SSP5‐8.5 scenario. However, contrasting trends emerge among predators across functional groups and regions of South America, Southern Africa, Australia and New Zealand. These variations highlight the need for species and regional‐specific management responses. We also project contrasting spatial mismatches between predators and prey: predators experiencing declines in suitable habitat tend to exhibit greater overlap with their prey in future scenarios, whereas those with expanding suitable habitat show reduced spatial overlap with their prey. This study provides valuable insights that can inform spatial management strategies in response to climate change and illustrate how climate change may weaken species' ability to adapt to climate‐driven environmental changes due to trophic disruptions.

Fish and tips: Historical and projected changes in commercial fish species' habitat suitability in the Southern Hemisphere - Maria Bas; Jazel Ouled-Cheikh; Laura Julià; Alba Fuster-Alonso; David March; Francisco Ramírez; Luis Cardona; Marta Coll (Science of The Total Environment, 2024)

Extension during the Liebig Orogeny: Revised tectonic setting of Paleoproterozoic central Australia - Samantha March; Martin Hand; Laura Morrissey; David Kelsey (Gondwana Research, 2024)

Omics biomarkers and an approach for their practical implementation to delineate health status for personalized nutrition strategies - Jaap Keijer; Xavier Escoté; Sebastià Galmés; Andreu Palou-March; Francisca Serra; Mona Adnan Aldubayan; Kristina Pigsborg; Faidon Magkos; Ella J. Baker; Philip C. Calder; Joanna Góralska; Urszula Razny; et al. (Critical Reviews in Food Science and Nutrition, 2024)

Use of bird‐borne radar to examine shearwater interactions with legal and illegal fisheries - Leia Navarro‐Herrero; Sarah Saldanha; Teresa Militão; Diego Vicente‐Sastre; David March; Jacob González‐Solís (Conservation Biology, 2024)
Seabirds interact with fishing vessels to consume fishing discards and baits, sometimes resulting in incidental capture (bycatch) and the death of the bird, which has clear conservation implications. To understand seabird–fishery interactions at large spatiotemporal scales, researchers are increasing their use of simultaneous seabird and fishing vessel tracking. However, vessel tracking data can contain gaps due to technical problems, illicit manipulation, or lack of adoption of tracking monitoring systems. These gaps might lead to underestimating the fishing effort and bycatch rates and jeopardize the effectiveness of marine conservation. We deployed bird‐borne radar detector tags capable of recording radar signals from vessels. We placed tags on 88 shearwaters ( Calonectris diomedea , Calonectris borealis , and Calonectris edwardsii ) that forage in the northwestern Mediterranean Sea and the Canary Current Large Marine Ecosystem. We modeled vessel radar detections registered by the tags in relation to gridded automatic identification system (AIS) vessel tracking data to examine the spatiotemporal dynamics of seabird–vessel interactions and identify unreported fishing activity areas. Our models showed a moderate fit (area under the curve >0.7) to vessel tracking data, indicating a strong association of shearwaters to fishing vessels in major fishing grounds. Although in high‐marine‐traffic regions, radar detections were also driven by nonfishing vessels. The tags registered the presence of potential unregulated and unreported fishing vessels in West African waters, where merchant shipping is unusual but fishing activity is intense. Overall, bird‐borne radar detectors showed areas and periods when the association of seabirds with legal and illegal fishing vessels was high. Bird‐borne radar detectors could improve the focus of conservation efforts.

Geospatial identification of stakeholders to support dynamic ocean management in transboundary areas - Federico Fabbri; Jean-Noël Druon; Brendan J. Godley; David March (Marine Policy, 2024)

Future climate‐induced distribution shifts in a sexually dimorphic key predator of the Southern Ocean - Jazel Ouled‐Cheikh; David March; Renato Borras‐Chavez; Massimiliano Drago; Michael E. Goebel; José M. Fariña; Manel Gazo; Marta Coll; Luis Cardona (Global Change Biology, 2024)
The response to climate change in highly dimorphic species can be hindered by differences between sexes in habitat preferences and movement patterns. The Antarctic fur seal, Arctocephalus gazella , is the most abundant pinniped in the Southern Hemisphere, and one of the main consumers of Antarctic krill, Euphausia superba , in the Southern Ocean. However, the populations breeding in the Atlantic Southern Ocean are decreasing, partly due to global warming. Male and female Antarctic fur seals differ greatly in body size and foraging ecology, and little is known about their sex‐specific responses to climate change. We used satellite tracking data and Earth System Models to predict changes in habitat suitability for male and female Antarctic fur seals from the Western Antarctic Peninsula under different climate change scenarios. Under the most extreme scenario (SSP5‐8.5; global average temperature +4.4°C projected by 2100), suitable habitat patches will shift southward during the non‐breeding season, leading to a minor overall habitat loss. The impact will be more pronounced for females than for males. The reduction of winter foraging grounds might decrease the survival of post‐weaned females, reducing recruitment and jeopardizing population viability. During the breeding season, when males fast on land, suitable foraging grounds for females off the South Shetland Islands will remain largely unmodified, and new ones will emerge in the Bellingshausen Sea. As Antarctic fur seals are income breeders, the foraging grounds of females should be reasonably close to the breeding colony. As a result, the new suitable foraging grounds will be useful for females only if nearby beaches currently covered by sea ice emerge by the end of the century. Furthermore, the colonization of these new, ice‐free breeding locations might be limited by strong female philopatry. These results should be considered when managing the fisheries of Antarctic krill in the Southern Ocean.

Movement pathways and habitat use of blue sharks (Prionace glauca) in the Western Mediterranean Sea: Distribution in relation to environmental factors, reproductive biology, and conservation issues - François Poisson; Hervé Demarcq; Sylvain Coudray; Jens Bohn; Juan Antonio Camiñas; Jean-Marc Groul; David March (Fisheries Research, 2024)

Hidden demographic impacts of fishing and environmental drivers of fecundity in a sea turtle population - Michael J. Roast; Samir Martins; Lourdes Fernández‐Peralta; José Carlos Báez; Ahmed Diame; David March; Jazel Ouled‐Cheikh; Adolfo Marco; Jacob González‐Solís; Luis Cardona (Conservation Biology, 2023)
Fisheries bycatch is a critical threat to sea turtle populations worldwide, particularly because turtles are vulnerable to multiple gear types. The Canary Current is an intensely fished region, yet there has been no demographic assessment integrating bycatch and population management information of the globally significant Cabo Verde loggerhead turtle ( Caretta caretta ) population. Using Boa Vista island (Eastern Cabo Verde) subpopulation data from capture–recapture and nest monitoring (2013–2019), we evaluated population viability and estimated regional bycatch rates (2016–2020) in longline, trawl, purse‐seine, and artisanal fisheries. We further evaluated current nesting trends in the context of bycatch estimates, existing hatchery conservation measures, and environmental (net primary productivity) variability in turtle foraging grounds. We projected that current bycatch mortality rates would lead to the near extinction of the Boa Vista subpopulation. Bycatch reduction in longline fisheries and all fisheries combined would increase finite population growth rate by 1.76% and 1.95%, respectively. Hatchery conservation increased hatchling production and reduced extinction risk, but alone it could not achieve population growth. Short‐term increases in nest counts (2013–2021), putatively driven by temporary increases in net primary productivity, may be masking ongoing long‐term population declines. When fecundity was linked to net primary productivity, our hindcast models simultaneously predicted these opposing long‐term and short‐term trends. Consequently, our results showed conservation management must diversify from land‐based management. The masking effect we found has broad‐reaching implications for monitoring sea turtle populations worldwide, demonstrating the importance of directly estimating adult survival and that nest counts might inadequately reflect underlying population trends.

Policy sequencing for early-stage transition dynamics – A process model and comparative case study in the water sector - Katrin Pakizer; Eva Lieberherr; Megan Farrelly; Peter M. Bach; David Saurí; Hug March; Miriam Hacker; Christian Binz (Environmental Innovation and Societal Transitions, 2023)

Priorities for Mediterranean marine turtle conservation and management in the face of climate change - Antonios D. Mazaris; Charalampos Dimitriadis; Maria Papazekou; Gail Schofield; Aggeliki Doxa; Anastasia Chatzimentor; Oguz Turkozan; Stelios Katsanevakis; Aphrodite Lioliou; Sara Abalo-Morla; Mustapha Aksissou; Antonella Arcangeli; et al. (Journal of Environmental Management, 2023)

Stakeholder perceptions of the socio-ecological role of nature-based solutions in the Les Glòries Park, Barcelona - Andrea Nóblega-Carriquiry; Hug March; David Sauri (Urban Forestry & Urban Greening, 2023)

Spatial distribution of the demersal chondrichthyan community from the western Mediterranean trawl bycatch - David Ruiz-García; Juan A. Raga; David March; Ana I. Colmenero; Federico Quattrocchi; Joan B. Company; Laura Recasens; Claudio Barría (Frontiers in Marine Science, 2023)
Introduction Chondrichthyans (sharks, batoids and chimaeras) play key roles in the regulation of marine food webs dynamics. However, more than half of the assessed species in the Mediterranean are threatened, primarily by fishing pressure and compounded by habitat degradation and climate change. Nevertheless, there is an important knowledge gap in identifying the underlying drivers of their community structure and spatial distribution. Methods and Results We provide insights into the current bycatch rates of chondrichthyans in the western Mediterranean commercial bottom trawling fishery by accurately depicting the unaltered practices of the local fleet. A total of 17 species were recorded in the studied fishing grounds (ranging from 50 to 800 m deep), including 7 sharks, 9 batoids, and 1 chimaera, although the total catch was dominated by few species. Furthermore, we tested the effect of environmental and fishing-related factors on multiple community descriptors by using analysis of community structure (multidimensional scaling and analysis of similitude) and generalized linear mixed models to further understand the drivers of the chondrichthyan community distribution and structure. This study revealed the importance of combining environmental and anthropogenic drivers to further understand the spatial distribution patterns of chondrichthyan communities. Our results indicate that depth was the main driver of the community structure, with deeper areas within the fishing grounds hosting a higher diversity. Sea bottom temperature and substrate type also influenced the distribution of the community, with substrate effects changing depending on the intensity of fishing pressure. In all cases, density, biomass, and diversity of chondrichthyans were negatively impacted by increasing fishing effort. Discussion Understanding the drivers of the structure and distribution of the chondrichthyan community is crucial to understand the potential impacts that increased fishing pressure, habitat loss and global change may entail. The ongoing challenges that the Mediterranean chondrichthyans and their ecosystems are facing highlights the need for continued monitoring and improved chondrichthyan-focused fisheries management.

Toward a common approach for assessing the conservation status of marine turtle species within the european marine strategy framework directive - Fanny Girard; Alexandre Girard; Jonathan Monsinjon; Antonella Arcangeli; Eduardo Belda; Luis Cardona; Paolo Casale; Sidonie Catteau; Léa David; Florence Dell’Amico; Delphine Gambaiani; Marc Girondot; et al. (Frontiers in Marine Science, 2022)
Environmental policies, including the European Marine Strategy Framework Directive (MSFD), generally rely on the measurement of indicators to assess the good environmental status (GES) and ensure the protection of marine ecosystems. However, depending on available scientific knowledge and monitoring programs in place, quantitative GES assessments are not always feasible. This is specifically the case for marine turtle species, which are listed under the Biodiversity Descriptor of the MSFD. Relying on an expert consultation, the goal of this study was to develop indicators and a common assessment approach to be employed by European Union Member States to evaluate the status of marine turtle populations in the frame of the MSFD. A dedicated international expert group was created to explore and test potential assessment approaches, in coherence with other environmental policies (i.e. Habitats Directive, OSPAR and Barcelona Conventions). Following a series of workshops, the group provided recommendations for the GES assessment of marine turtles. In particular, indicators and assessment methods were defined, setting a solid basis for future MSFD assessments. Although knowledge gaps remain, data requirements identified in this study will guide future data collection initiatives and inform monitoring programs implemented by EU Member States. Overall this study highlights the value of international collaboration for the conservation of vulnerable species, such as marine turtles.

Basin-wide estimates of loggerhead turtle abundance in the Mediterranean Sea derived from line transect surveys - Andrew DiMatteo; Ana Cañadas; Jason Roberts; Laura Sparks; Simone Panigada; Olivier Boisseau; Anna Moscrop; Caterina Maria Fortuna; Giancarlo Lauriano; Draško Holcer; Hélène Peltier; Vincent Ridoux; et al. (Frontiers in Marine Science, 2022)
Loggerhead turtles are a globally vulnerable species of marine turtle. Broad-scale patterns of distribution and abundance can provide regional managers a tool to effectively conserve and manage this species at basin and sub-basin scales. In this study, combined aerial and shipboard line transect survey data collected between 2003 and 2018 were used to estimate distribution and abundance throughout the Mediterranean Sea. Approximately 230,000 linear kilometers of survey effort, from seven different surveying organizations were incorporated into a generalized additive model to relate loggerhead density on survey segments to environmental conditions. Two spatial density models estimating loggerhead density, abundance, and distribution were generated – one a long-term annual average covering 2003-2018 and another covering the summer of 2018, when a basin-wide aerial survey, the Agreement on the Conservation of Cetaceans of the Black Sea, Mediterranean Sea and Contiguous Atlantic Area Survey Initiative, was performed. Both models were adjusted for availability bias using dive data from loggerhead turtles tagged with time depth recorders. Mean abundance for the long-term average model was estimated as 1,201,845 (CV=0.22). The summer 2018 abundance estimate was 789,244 turtles and covered a smaller area than the long-term average. These estimates represent the first basin-wide estimates of abundance for loggerhead turtles in the Mediterranean not based on demographic models. Both models predicted similar distributions, with higher abundance predicted in the northern Adriatic Sea, central Mediterranean basin, Tyrrhenian Sea, and south of the Balearic Islands. Lower densities were predicted in the eastern Mediterranean Sea and the Aegean Sea. The highest density areas generally did not coincide with previously established adult loggerhead turtle foraging areas, which are typically neritic, indicating the models are predominantly predicting oceanic distributions, where most of the survey effort occurred. Juvenile loggerhead turtles are predominantly oceanic and comprise most of the population, but care must be taken when using these models as they may not accurately predict distribution of neritic foraging areas, where subadult and adult loggerheads can often be found. Despite this limitation, these models represent a major step forward for conservation planning and understanding basin-wide distribution and abundance patterns of this species.

Animal Borne Ocean Sensors – AniBOS – An Essential Component of the Global Ocean Observing System - Clive R. McMahon; Fabien Roquet; Sophie Baudel; Mathieu Belbeoch; Sophie Bestley; Clint Blight; Lars Boehme; Fiona Carse; Daniel P. Costa; Michael A. Fedak; Christophe Guinet; Robert Harcourt; et al. (Frontiers in Marine Science, 2021)
Marine animals equipped with biological and physical electronic sensors have produced long-term data streams on key marine environmental variables, hydrography, animal behavior and ecology. These data are an essential component of the Global Ocean Observing System (GOOS). The Animal Borne Ocean Sensors (AniBOS) network aims to coordinate the long-term collection and delivery of marine data streams, providing a complementary capability to other GOOS networks that monitor Essential Ocean Variables (EOVs), essential climate variables (ECVs) and essential biodiversity variables (EBVs). AniBOS augments observations of temperature and salinity within the upper ocean, in areas that are under-sampled, providing information that is urgently needed for an improved understanding of climate and ocean variability and for forecasting. Additionally, measurements of chlorophyll fluorescence and dissolved oxygen concentrations are emerging. The observations AniBOS provides are used widely across the research, modeling and operational oceanographic communities. High latitude, shallow coastal shelves and tropical seas have historically been sampled poorly with traditional observing platforms for many reasons including sea ice presence, limited satellite coverage and logistical costs. Animal-borne sensors are helping to fill that gap by collecting and transmitting in near real time an average of 500 temperature-salinity-depth profiles per animal annually and, when instruments are recovered (∼30% of instruments deployed annually, n = 103 ± 34), up to 1,000 profiles per month in these regions. Increased observations from under-sampled regions greatly improve the accuracy and confidence in estimates of ocean state and improve studies of climate variability by delivering data that refine climate prediction estimates at regional and global scales. The GOOS Observations Coordination Group (OCG) reviews, advises on and coordinates activities across the global ocean observing networks to strengthen the effective implementation of the system. AniBOS was formally recognized in 2020 as a GOOS network. This improves our ability to observe the ocean’s structure and animals that live in them more comprehensively, concomitantly improving our understanding of global ocean and climate processes for societal benefit consistent with the UN Sustainability Goals 13 and 14: Climate and Life below Water. Working within the GOOS OCG framework ensures that AniBOS is an essential component of an integrated Global Ocean Observing System.

Towards the integration of animal‐borne instruments into global ocean observing systems - David March; Lars Boehme; Joaquín Tintoré; Pedro Joaquín Vélez‐Belchi; Brendan J. Godley (Global Change Biology, 2020)
Marine animals are increasingly instrumented with environmental sensors that provide large volumes of oceanographic data. Here, we conduct an innovative and comprehensive global analysis to determine the potential contribution of animal‐borne instruments (ABI) into ocean observing systems (OOSs) and provide a foundation to establish future integrated ocean monitoring programmes. We analyse the current gaps of the long‐term Argo observing system (>1.5 million profiles) and assess its spatial overlap with the distribution of marine animals across eight major species groups (tuna and billfishes, sharks and rays, marine turtles, pinnipeds, cetaceans, sirenians, flying seabirds and penguins). We combine distribution ranges of 183 species and satellite tracking observations from >3,000 animals. Our analyses identify potential areas where ABI could complement OOS. Specifically, ABI have the potential to fill gaps in marginal seas, upwelling areas, the upper 10 m of the water column, shelf regions and polewards of 60° latitude. Our approach provides the global baseline required to plan the integration of ABI into global and regional OOS while integrating conservation and ocean monitoring priorities.

Modeling environmental influence on Atlantic bluefin tuna bycatch by Mexican longliners in the Gulf of Mexico - Alberto Abad‐Uribarren; Sofía Ortega‐García; David March; Antonio Medina (Fisheries Oceanography, 2019)
Atlantic bluefin tuna (ABFT) stocks have been considered overfished over the last decades, especially the western stock, whose main spawning grounds are in the Gulf of Mexico (GoM). Despite the current measures implemented, spawner bycatch by the longline fleet targeting yellowfin tuna (YFT) may explain the lack of recovery of local stocks. This situation demands the implementation of appropriate spatiotemporal management strategies to minimize bluefin bycatch in the GoM, which involves knowledge in depth of its distribution and environmental forcing. Using catch and effort data from the Mexican commercial longline fleet with 100% scientific observer coverage from 1999 to 2012 and satellite derived environmental data, this study investigated the influence of environmental conditions on catch per unit effort (CPUE) of ABFT and YFT. General additive models (GAMs) were fitted using a negative binomial distribution and applying Akaike information criterion (AIC) to select the best model. Bluefin CPUE exhibited a marked seasonality, reaching higher values in February and March while YFT catches occurred throughout the year. Two main locations were identified with higher ABFT bycatch rates, Campeche Bay and the western‐central area of the GoM. Higher ABFT CPUE was significantly associated with areas with negative sea level anomalies and low sea surface temperatures, characteristic of cyclonic eddies. Instead, YFT CPUE showed a lesser environmental influence in its distribution. To our knowledge, the patterns shown in this study provide the first in‐depth approach to understand ABFT bycatch in Mexican waters, which will help in further development of adequate management strategies.

A broader approach to understanding urbanization effects on freshwater turtles: reply to Lambert and Steen 2019 - David R. Bowne; Bradley J. Cosentino; Laurel J. Anderson; Sandra Cooke; Jerald J. Dosch; Danielle Garneau; Todd S. Fredericksen; Mary Beth Kolozsvary; Erin S. Lindquist; James G. March; Rebecca A. Urban; Craig R. Zimmermann (Conservation Biology, 2019)

Challenges for Sustained Observing and Forecasting Systems in the Mediterranean Sea - Joaquín Tintoré; Nadia Pinardi; Enrique Álvarez-Fanjul; Eva Aguiar; Diego Álvarez-Berastegui; Marco Bajo; Rosa Balbin; Roberto Bozzano; Bruno Buongiorno Nardelli; Vanessa Cardin; Benjamin Casas; Miguel Charcos-Llorens; et al. (Frontiers in Marine Science, 2019)

Climate change does not affect the seafood quality of a commonly targeted fish - Melinda A. Coleman; Peter Butcherine; Brendan P. Kelaher; Matt K. Broadhurst; Duane T. March; Euan J. Provost; Jamie David; Kirsten Benkendorff (Global Change Biology, 2019)
Climate change can affect marine and estuarine fish via alterations to their distributions, abundances, sizes, physiology and ecological interactions, threatening the provision of ecosystem goods and services. While we have an emerging understanding of such ecological impacts to fish, we know little about the potential influence of climate change on the provision of nutritional seafood to sustain human populations. In particular, the quantity, quality and/or taste of seafood may be altered by future environmental changes with implications for the economic viability of fisheries. In an orthogonal mesocosm experiment, we tested the influence of near‐future ocean warming and acidification on the growth, health and seafood quality of a recreationally and commercially important fish, yellowfin bream ( Acanthopagrus australis ). The growth of yellowfin bream significantly increased under near‐future temperature conditions (but not acidification), with little change in health (blood glucose and haematocrit) or tissue biochemistry and nutritional properties (fatty acids, lipids, macro‐ and micronutrients, moisture, ash and total N). Yellowfin bream appear to be highly resilient to predicted near‐future ocean climate change, which might be facilitated by their wide spatio‐temporal distribution across habitats and broad diet. Moreover, an increase in growth, but little change in tissue quality, suggests that near‐future ocean conditions will benefit fisheries and fishers that target yellowfin bream. The data reiterate the inherent resilience of yellowfin bream as an evolutionary consequence of their euryhaline status in often environmentally challenging habitats and imply their sustainable and viable fisheries into the future. We contend that widely distributed species that span large geographic areas and habitats can be “climate winners” by being resilient to the negative direct impacts of near‐future oceanic and estuarine climate change.

Effects of urbanization on the population structure of freshwater turtles across the United States - David R. Bowne; Bradley J. Cosentino; Laurel J. Anderson; Christopher P. Bloch; Sandra Cooke; Patrick W. Crumrine; Jason Dallas; Alexandra Doran; Jerald J. Dosch; Daniel L. Druckenbrod; Richard D. Durtsche; Danielle Garneau; et al. (Conservation Biology, 2018)
Landscape‐scale alterations that accompany urbanization may negatively affect the population structure of wildlife species such as freshwater turtles. Changes to nesting sites and higher mortality rates due to vehicular collisions and increased predator populations may particularly affect immature turtles and mature female turtles. We hypothesized that the proportions of adult female and immature turtles in a population will negatively correlate with landscape urbanization. As a collaborative effort of the Ecological Research as Education Network (EREN), we sampled freshwater turtle populations in 11 states across the central and eastern United States. Contrary to expectations, we found a significant positive relationship between proportions of mature female painted turtles ( Chrysemys picta ) and urbanization. We did not detect a relationship between urbanization and proportions of immature turtles. Urbanization may alter the thermal environment of nesting sites such that more females are produced as urbanization increases. Our approach of creating a collaborative network of scientists and students at undergraduate institutions proved valuable in terms of testing our hypothesis over a large spatial scale while also allowing students to gain hands‐on experience in conservation science.

Perception of the effects of climate change in winter and summer tourist areas: the Pyrenees and the Catalan and Balearic coasts, Spain - Hug March; David Saurí; Joan Carles Llurdés (Regional Environmental Change, 2014)

Rising Temperatures and Dwindling Water Supplies? Perception of Climate Change Among Residents of the Spanish Mediterranean Tourist Coastal Areas - Hug March; David Saurí; Jorge Olcina (Environmental Management, 2014)

Water conservation campaigns and citizen perceptions: the drought of 2007–2008 in the Metropolitan Area of Barcelona - Hug March; Laia Domènech; David Saurí (Natural Hazards, 2013)

Parasites boost productivity: effects of mistletoe on litterfall dynamics in a temperate Australian forest - Wendy A. March; David M. Watson (Oecologia, 2007)